Distress, trauma, and recovery: Adjustment to first episode psychosis. (14th June 2012) - Tan, Ranil; Gould, Rachel V.; Combes, Helen; Lehmann, Sarah
<x xml:space="preserve">Abstract</x> Objective. To understand the experiences that people with early psychosis are adjusting to and their perceived barriers to recovery. Method. Semi‐structured interviews were conducted with eight participants. Grounded Theory was applied to the design and analysis. Sampling and coding ceased when saturation of the data was reached. Respondent validation was sought from participants. Results. A theoretical model was developed using Strauss and Corbin's (1998) framework. A core category of distress was elicited, which was evident in all participants' accounts of their recovery. Overall six main categories were identified and it was proposed that individuals were adjusting to the distress of past experiences, uncertainty, a challenged identity, being in a psychiatric system, the reaction of others and social disadvantage. Conclusions. Recovery from the distress and trauma of early psychosis does not simply involve adjustment to and recovery from a single experience or set of symptoms. The results are discussed in relation to trauma, developmental, and social inequality frameworks. Specific implications for clinical practice include incorporating the findings within formulations, developing interventions that focus on trauma, identity, and uncertainty as well as addressing the social and systemic issues identified. Practitioner Points Recovery from early psychosis is multi‐faceted. Psychological formulations should seek to consider individual, social, and systemic factors influencing an individual's distress to more fully conceptualize what an individual's adjustment to early psychosis may involve. Services and wider systems should consider iatrogenic processes, which may contribute to and maintain the distress experienced by those with early psychosis. Education programmes that look to contextualize psychosis within a meaningful framework may help to develop understanding within wider society where a lack of knowledge and understanding serves to reinforce an individual's sense of exclusion and difference.